2018
DOI: 10.5089/9781484345351.001
|View full text |Cite
|
Sign up to set email alerts
|

More Slack than Meets the Eye? Recent Wage Dynamics in Advanced Economies

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
(19 reference statements)
2
22
0
Order By: Relevance
“…In our own work, we consider some cross-country panel regressions of OECD countries, using hourly wage growth as the dependent variable. A model in the style of Hong et al (2018) uses lagged inflation, productivity growth, the unemployment rate, and the change in the unemployment rate as explanatory variables. However, we find that when a variable for solo self-employment is added to the explanatory variables, it has an additional statistically significant effect in line with the notion that it too reflects some degree of slack in the labor market.…”
Section: Wage Moderationmentioning
confidence: 99%
“…In our own work, we consider some cross-country panel regressions of OECD countries, using hourly wage growth as the dependent variable. A model in the style of Hong et al (2018) uses lagged inflation, productivity growth, the unemployment rate, and the change in the unemployment rate as explanatory variables. However, we find that when a variable for solo self-employment is added to the explanatory variables, it has an additional statistically significant effect in line with the notion that it too reflects some degree of slack in the labor market.…”
Section: Wage Moderationmentioning
confidence: 99%
“…In the post Great Recession years since 2008 we show measures of underemployment replaces unemployment as the primary measure of labor market slack. a) Cross-country evidence Important recent work by Hong et al (2018) from the IMF across 30 countries has shown that the IPTR -expressed as a percent of total employment -enters significantly negative in wage change equations. In the same equations the unemployment rate and the change in the unemployment rates are also significantly negative.…”
Section: Non-unionmentioning
confidence: 99%
“…In the post Great Recession years since 2008 we show measures of underemployment replaces unemployment as the primary measure of labor market slack. a) Cross-country evidence Important recent work by Hong et al (2018) from the IMF across 30 countries has shown that the IPTRexpressed as a percent of total employment -enters significantly negative in wage change equations. In the same equations the unemployment rate and the change in the unemployment rates are also significantly negative.…”
Section: Non-unionmentioning
confidence: 99%
“…We are grateful to Hong et al (2018) for providing us with their data. We then mapped onto it our underemployment rates for 19 of the countries in Table 3 and Table 4, making 275 observations in all.…”
Section: Non-unionmentioning
confidence: 99%